Indications and Outcomes of Penetrating Keratoplasty in Infants and Children of Beijing, China. Issue 10 (October 2018) - Zhang, Yingnan; Liu, Yang; Liang, Qingfeng; Miao, Sen; Lin, Qi; Zhang, Jing; Pan, Zhiqiang; Lu, Qingxian
Abstract : Purpose: To retrospectively investigate the indications and outcomes of pediatric penetrating keratoplasty (PKP) and to explore factors that affect graft survival. Methods: Patients who had undergone PKP from May 2010 to December 2016, aged ⩽12 years were categorized as infants (≥3 months and <4 years) or children (≥4 years and ⩽12 years). Clinical data including patient demographics, indications, surgical procedures, postoperative follow-up, and graft clarity were recorded and analyzed. Results: Among 160 eyes of 146 patients, 79 eyes and 81 eyes were treated from the infant and child groups, respectively, and followed up for 33.7 ± 21.7 months (range, 6 months to 7 years). The most common indication for PKP was congenital corneal opacity (71.9%). The survival rate of all corneal grafts was 68.1%. The rejection reaction rate was 33.8%. More children than infants underwent PKP that was combined with other intraocular surgeries ( P < 0.05). The graft failures were in the regraft (52.0%), congenital opacities (30.4%), and acquired opacities (15.0%) groups. The rate of graft failure in patients who received PKP combined with other intraocular surgery (40.0%) was higher than those who received PKP only (30.0%). The univariate logistic regression analysis revealed that the graft failure was associated with the graft indication ( P < 0.05). Conclusions: The most common indication for PKP in children younger than 12 years was congenital corneal opacity in Beijing, China. The graft survival was 68.1%, with a mean follow-up of 33.7 months. Graft failure was associated with the indication.